Effect of lignin-based amphiphilic polymers on the cellulase adsorption and enzymatic hydrolysis kinetics of cellulose. (1st March 2019) - Lin, Xuliang; Wu, Linjun; Huang, Siqi; Qin, Yanlin; Qiu, Xueqing; Lou, Hongming
Graphical abstract: Highlights: Interaction of lignin amphiphilic polymers and cellulase was studied by QCM-D. Lignosulfonate combined with cellulase by electrostatic attractive interaction. EHL-PEG-Cellulase hydrolysis cellulose film through hollow way. Strategy to enhance hydrolysis by lignin amphiphilic polymers was proposed. Abstract: The origin, amount, hydrophilicity, charge, molecular weight and its distribution of lignin have significant influences on the enzymatic hydrolysis of lignocellulose. The enzymatic hydrolysis of lignocellulose was essentially enhanced by lignin-based polyoxyethylene ether (EHL-PEG), whereafter followed by PEG4600 and lignosulfonate (LS). The effect of LS, EHL-PEG and PEG4600 on the adsorption and enzymatic hydrolysis kinetics of cellulase on the gold surface and cellulose film was investigated by Quartz Crystal Microbalance with dissipation monitoring (QCM-D). Results showed that the interaction of LS or EHL-PEG with cellulase was electrostatic attractive and hydrophobic effect, respectively, and formed hydrophilic cellulase aggregates. LS-Cellulase peeled off the cellulose film layer by layer, while the hydrophobic phenylpropane structure of EHL-PEG-Cellulase acted as a cellulose binding domain to hydrolysis cellulose through "Hollow" effect and made cellulose become more loose and swollen. At last, a strategy to enhance the enzymatic hydrolysis of lignocellulose by lignin-based amphiphilic polymers was proposed as well.